QUANTITATIVE APPROACH; THE EFFECT OF OUTDOOR STUDY IN TEACHING WRITING - saasa, saasa; Susanto, Teguh Adhyatma; Safrul, Siti Rahmayanti Safrul Rahmayanti; Untung, Untung (The Ellite of Unira, 2025)
The purpose of this study is to determine the influence or effect of using the Outdoor Study method on students' writing skills. The research method used in this study is quantitative method, which allows researchers to measure changes objectively based on numerical data. This research involves the process of giving treatment to students through learning outside the classroom with the Outdoor Study approach. After the treatment was given, there was a significant change in students' test results. The highest score in the pre-test was initially 67, then after the post-test it increased to 85. In addition, the average value (mean) in the pre-test of 62.23 also increased quite sharply to 79.20 in the post-test. These results show that the use of the Outdoor Study method can significantly improve students' writing skills. This finding is expected to be an input for teachers to apply more varied, active, and contextual learning approaches.